Household decision-making in Malaysia: the ethnic dimension - Abdullah Yusof, Selamah (Springer, 2015)
Household financial decision-making process is an important issue as it has shown to have implications on key development outcomes such as child health and education,nutrition, expenditure, and allocation of labor. Women’s ability to have control over household finances and decisions also reflects, to some extent, their level of empowerment. This study focuses on the effect of ethnicity on decision making in a household. There is relatively limited research in this area and data obtained from households in Malaysia, a multi-ethnic and multi-cultural country, provides an opportunity for an in-depth examination of the ethnic dimension. The data is obtained from a random survey of 672 Malaysian urban households of which the selection of sample was strictly determined by the Department of Statistics Malaysia to ensure randomness. The findings show that there are differences across households of different ethnicity. Chinese households are found to be more traditional and patriarchal where decisions on household financial matters are more husband-dominated. Education contributes positively in giving women more control over household finances and decision-making. The results of the study highlight the importance of ethnicity in determining the level of household bargaining and decision making power which has implications on strategies in marketing as well as national policies. Thus, any substantive and policy inferences in relations to women’s empowerment must take into account the socio-cultural aspects, rather than based on overall national level analyses. The finding that education plays a significant role in empowering women is a positive outcome. With more Malaysian women attaining higher levels of education and becoming part of the workforce, their level of empowerment and wellbeing will improve and consequently provide a positive impact on key development outcomes of the country